2019
DOI: 10.1002/cssc.201900886
|View full text |Cite
|
Sign up to set email alerts
|

A Ball‐Milling‐Enabled Reformatsky Reaction

Abstract: An operationally simple one‐jar one‐step mechanochemical Reformatsky reaction using in situ generated organozinc intermediates under neat grinding conditions has been developed. Notable features of this reaction protocol are that it requires no solvent, no inert gases, and no pre‐activation of the bulk zinc source. The developed process is demonstrated to have good substrate scope (39–82 % yield) and is effective irrespective of the initial morphology of the zinc source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 74 publications
(18 reference statements)
0
32
0
Order By: Relevance
“…For example, the use of ball milling techniques has enabled the use of oxygen-sensitive metal species in air without the need for glove-box and Schlenk-line techniques. [163,164,218] Consequently, achieving a degree of operational simplicity which in turn could minimize the potential for accidents (GC 12). Moreover, although some studies have reported that materials such as azides, [219] diazonium salts, [220] or contact-unstable mixtures [221] undergo ball milling reactions without incident, precaution is always recommended!…”
Section: Gc 12: Safer Chemistry and Accident Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of ball milling techniques has enabled the use of oxygen-sensitive metal species in air without the need for glove-box and Schlenk-line techniques. [163,164,218] Consequently, achieving a degree of operational simplicity which in turn could minimize the potential for accidents (GC 12). Moreover, although some studies have reported that materials such as azides, [219] diazonium salts, [220] or contact-unstable mixtures [221] undergo ball milling reactions without incident, precaution is always recommended!…”
Section: Gc 12: Safer Chemistry and Accident Preventionmentioning
confidence: 99%
“…This strategy clearly simplifies the synthetic route toward organozinc species for example in the Negishi cross‐coupling reaction by avoiding derivatization of the substrates through classical transmetalation steps (Scheme 9a) [163] . The application of this mechanochemical approach has also led to more sustainable versions of classic C−C bond formation protocols such as the Reformatsky reaction [164a] and the Barbier‐type allylation reaction [164b] …”
Section: Mechanochemistry and The Twelve Principles Of Green Chemistrymentioning
confidence: 99%
“…Mechanochemistry has emerged as a versatile means to conduct reactions without bulk solvents, by shearing, grinding, or milling. Such reactions avoid bulk solvents and heat, offering a greener alternative to solution methods . However, mechanochemistry can also be a tool for reaction discovery and development, enabling the synthesis of previously inaccessible molecules, and offering transformations and selectivities that are not seen in solution .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, liquid-phase reactions are characterized by using bulk toxic organic solvents and harsh reaction conditions. With the need for cleaner, safer, and more sustainable chemical transformations, the use of mechanochemistry, which is identified by IUPAC as one of the 10 world-changing technologies [ 1 ] in chemical synthesis, has boomed over the past few decades and is rapidly becoming a powerful tool for environmentally friendly and sustainable synthesis of molecules and materials, including coordination, supramolecular, and covalent structures [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical ball-milling technique, an eco-friendly mechanochemical protocol, can not only promote solvent-free reactions and increase the reaction efficiency [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], even more attractively, but also alter chemical reactivity and selectivity compared to the solution-based counterparts, leading to different products, which draws forth the tantalizing hypothesis that some molecules can only be obtained by mechanochemistry [ 13 , 14 ]. For instance, Wang et al reported the reaction of [60]fullerene (C 60 ) and KCN under high-speed vibration ball milling (HSVM) for 30 min to unexpectedly afford fullerene dimer C 120 even after quenching with trifluoroacetic acid (TFA) [ 15 ], while the same reaction in a mixture of 1,2-dichlorobenzene (ODCB) and N , N -dimethylformamidal (DMF) reported earlier by Wudl and coworkers afforded a different fullerene product, C 60 H(CN) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%